Top 10 Dubai & Abu Dhabi - Dunston, Lara; Monaghan, Sarah (London Dorling Kindersley Limited, 2014)
Discusses lodging, dining, and entertainment in Dubai and Abu Dhabi, along with information on trip planning, security, and shopping
Includes index
2
NEW
Keywords: Dubai (United Arab Emirates) -- Guidebooks